Arterial Thoracic Outlet Syndrome and Cerebellar Infarction Following a Stress Fracture of the First Rib and Extensive Callus Formation: A Case Report. Issue 3 (July 2017) - Suehara, Yoshiyuki; Imashimizu, Kota; Miyamoto, Nobukazu; Uehara, Hirohisa; Tanabe, Yu; Hattori, Nobutaka; Suzuki, Kenji; Saito, Tsuyoshi; Kaneko, Kazuo
Abstract : Case: Stress fractures of the first rib rarely have been reported in association with sports activities. We report a case of a cerebellar infarction that possibly was associated with arterial thoracic outlet syndrome (aTOS) that developed as a result of extensive callus formation in a young baseball player with a stress fracture of the first rib. Conclusion: According to the literature, almost all cases of stress fracture in the first rib have a relatively good prognosis, and there are only a few reports of TOS occurring as a rare late complication. To our knowledge, there have been no prior reports of cerebellar infarction associated with aTOS following a stress fracture of the first rib.